سلطة القاضي التقديرية في إنشاء عقد الزواج وحله : دراسة مقارنة بالقانون الأردني - عباس، عمر محمد; الرفاعي، جميلة عبدالقادر شعبان (الجامعة الإسلامية بغزة - عمادة البحث العلمي والدراسات العليا, 2018)
التأصيل الفقهي للمسائل وذكر أهم الأراء الفقهية وبيان الراجح ومن ثم التعريج عل مواد قانون الأحوال الشخصية الأردني التي تناولت هذه المسائل، ثم ذكر مدى سلطة القاضي، ودوره في إنشاء عقد الزواج وحله، وذلك لما يتمتع به القاضي من سلطة تخوله لذلك ، وتناول البحث بعض القضايا المستجدة في قانون الأحوال الشخصية الأردني، ومدى سلطة القاضي في الحد من المنازعات الأسرية، ومن هذه المسائل التي تناولها البحث مسألة تقدير العوض عن العدول عن الخطبة ، ومسألة زواج القاصرين، وتعدد الزوجات، وتقدير العوض عن الطلاق التعسفي والشقاق والنزاع، والخلع القضائي، وقد توصلت الدراسة أن للقاضي سلطة تقديرية في إنشاء عقد الزواج وحله في الفقه الإسلامي وقانون الأحوال الشخصية الأردني وهذه السلطة التقديرية تقوم على المصلحة، ومراعاة مقاصد الشريعة الإسلامية.
The purpose of this study is to clarify the authority of the discretionary judge in the establishment and dissolution of the marriage contract. In this study, it dealt with research through the jurisprudentialization of the issues and mentioned the most important jurisprudential opinions and the most correct views and then the articles on the Jordanian Personal Status Law, And his role in establishing and dissolving the marriage contract, because the judge has the power to do so. The study dealt with some of the new issues in the Jordanian Personal Status Law And the extent of the judge's power to limit family disputes. Among the issues discussed in this study is the question of how to compensate for the abandonment of the engagement, the issue of marriage of minors, polygamy and the estimation of the compensation for arbitrary divorce, dissension and conflict. The study concluded that the judge has discretion in establishing Marriage contract and its dissolution in Islamic jurisprudence and Jordanian personal status law. This discretionary authority is based on interest and observance of the purposes of Islamic law.
Keywords: السلطة القضائية -- السلطة التقديرية -- القوانين والتشريعات -- عقد الزواج -- الطلاق -- الأردن